Digitalization as a Factor for Development of the Target Arctic Subspaces - Alexey M. Fadeev; Igor V. Ilin; Anastasia I. Levina; Alissa S. Dubgorn; Polina A. Rukina (Арктика и Север)
The Arctic zone of the Russian Federation is a rich, attractive, but hard-to-reach region. The authors of the article believe that the current level of development of digital and data technologies can make a constructive contribution to overcoming some of the challenges of Arctic conquest. Since the Russian Arc-tic is a complexly structured macro-region, the authors rely on the division of the Arctic into seven target subspaces. The paper identifies the requirements of the target Arctic subspaces for digital technologies that could facilitate the process of Arctic exploration. The paper used the results of previous research by colleagues, traditional methods of scientific analysis combined with an interdisciplinary approach, and an architectural approach to the design of socio-economic systems to identify the requirements of the identified subspaces. Based on the analysis of the collected and summarized materials, seven models of motivational extensions were constructed for each of the identified Arctic subspaces, summarizing information about the goal-setting of each subspace. Among other goal-setting factors, the requirements for digital technology services that would contribute to the development of each subspace were formulated. The resulting requirements contain both digital support needs common to all subspaces and those specific to each subspace due to its characteristics. As a result, the directions for effective implementation and use of digital technologies in the Russian Arctic were summarized.